Frauensuchtarbeit in Deutschland: Eine Bestandsaufnahme - Tödte, Martina; Bernard, Christiane (transcript, 2016)
What is the current status of services for women with dependency issues? What have they achieved? A critical survey and overview for researchers and practitioners.